2021
DOI: 10.1063/5.0041808
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of digital to analog switching in TaOx-based memristor device for neuromorphic applications

Abstract: An oxidizable metal diffusion barrier inserted between the active metal electrode and the switching layer decreases the electroforming voltage and enhances the switching stability and synaptic performances in TaOx-based conducting bridge memristor devices. The TiW barrier layer avoids an excessive metal ion diffusion into the switching layer whilst the TiWOx interfacial layer formed between the barrier and switching layer. It modulates the oxygen vacancy distribution at top interface and contributes to the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 36 publications
0
17
1
Order By: Relevance
“…[4] Resistive Random Access Memory (RRAM) or memristor is considered as one of the promising candidate for neuromorphic computing due to its CMOS compatibility, good data endurance, analog resistive switching, and multilevel cell (MLC) characteristics. [5,6] However, achieving analog switching with MLC characteristic and emulating stable synaptic behavior by applying AC pulses are still challenging in RRAM technology. Apart from achieving stable synaptic switching, fabrication of memristors on polymers/plastic is very difficult and crucial in order to minimize cost toward green and wearable electronics.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Resistive Random Access Memory (RRAM) or memristor is considered as one of the promising candidate for neuromorphic computing due to its CMOS compatibility, good data endurance, analog resistive switching, and multilevel cell (MLC) characteristics. [5,6] However, achieving analog switching with MLC characteristic and emulating stable synaptic behavior by applying AC pulses are still challenging in RRAM technology. Apart from achieving stable synaptic switching, fabrication of memristors on polymers/plastic is very difficult and crucial in order to minimize cost toward green and wearable electronics.…”
Section: Introductionmentioning
confidence: 99%
“…Saleem et al demonstrated a transformation of digital switching to analog switching in TaO x -based CBRAM devices by inserting an oxidizable metal diffusion barrier between the AE and switching layer [ 80 ]. The device without an additional barrier layer showed typical abrupt switching behavior ( Figure 12 a,b).…”
Section: Neuromorphic Computing Applicationsmentioning
confidence: 99%
“…Reprinted from Ref. [ 80 ]. ( h ) The I–V characteristics of an Ag nanoparticles-doped CNC-based CBRAM device showing analog switching and ( i ) its LTP/LTD characteristics.…”
Section: Figurementioning
confidence: 99%
“…A diffusion barrier is usually employed in this type of memristor device to control the atomic drift [24,25]. Aftab S. et al used an oxidizable metal TiW as a diffusion barrier layer inserted between the switching layer and active metal top electrode to transform TaOx-based memritor from digital set into analog [26]. Figure 7 shows the I-V curves and synaptic behavior of Cu/TaOx/TiN (device A) and Cu/TiW/TaOx/ TiN (device B) memristors.…”
Section: Cation Drift Barrier Layermentioning
confidence: 99%
“…Figure 7.Typical I-V curves and synaptic behavior of devices made without (device A) and with (device B) TiW barrier layer. Reprinted from[26].…”
mentioning
confidence: 99%